Decreased sensitivity of Neisseria gonorrhoeae to cefixime and ceftriaxone: Report of three cases in Bangrak hospital, Thailand - แสงสุวรรณ, วิชญ์; ลาวัง, รัตนา (Disease Control Journal, 2016)
Background : Treatment failure of Neisseria gonorrhoeae infection has been reported in USA, Japan and other European countries. Our case report focus on the surveillance of cefixime and cefriaxone susceptibility in Thailand. Objective: To observe the emergence of antibiotic resistance N. gonorrhoeae by interpreting of the MICs of cefixime and ceftriaxone. Material and Method: We conduct drug sensitivity for Neisseria gonorrhoeae, particularly cefixime and ceftriaxone Minimal inhibitory concentrations (MICs) of Neisseria gonorrhoeae by using E-test method in selective media. Result: The first case was heterosexual man came to hospital with symptoms of dysuria and discharge from urethra. The second case was woman who was the partner of first case came to hospital without any signs and symptoms. The third case was homosexual man came to hospital with generalized rash, no dysuria or discharge. All three cases, bacterial culture revealed β-lactamase negative N. gonorrhoeae. The MICs of cefixime were ranging from 0.064-0.125 μg/ml and the MICs of ceftriaxone were 0.064 μg/ml. All patients were treated and fully recovered. Conclusion: to all of the reported cases, N. gonorrhoeae strains were susceptible to cefixime and ceftriaxone, but there was an increase of MICs of cefixime and ceftriaxone which the highest MICs in Thailand. Every hospital should pay great attention on possible occurrence of resistant strains of gonorrhoeae. Further evaluation on cephalosporin MICs to N. gonorrhoeae should be implemented in patients who are not fully recovered by initial treatment.